Numerical investigation of the transferability of ductile fracture behavior between thin-walled surface-cracked pipe, curved wide plate (CWP) and single edge notched tension (SENT) specimens - Jang, Youn-Young; Kim, Ik-Joong; Huh, Nam-Su; Kim, Ki-Seok; Kim, Young-Pyo (Journal of mechanical science and technology, 2019)
Curved wide plate (CWP) and single edge notched tension (SENT) tests are commonly considered for determining the fracture toughnesses of high-strength line-pipe steel for the strain-based design. However, the tearing resistance relationship between these tests and actual thin-walled surface-cracked pipe has not been clearly established. The purpose of this study is to compare the crack growth characteristics of actual pipe, CWP and SENT using the local damage method, which is based on the Gurson-Tvergaard-Needleman (GTN) model. Small-scale testing of smooth round bar tensile and SENT specimens provides the information required to calibrate the damage parameters of the GTN model. Crack growth simulations are then conducted using the calibrated GTN model to evaluate the tearing resistance behaviors of various geometries. The tearing resistances of the CWP and the actual pipe are similar, whereas the SENT specimen exhibits a higher stress triaxiality. However, this tendency of SENT specimen changes as the crack propagates, which is related to the conservatism of the crack growth resistance curve. Therefore, it is necessary to identify the SENT test specimen usability and limitation via ductile damage simulations.